Synthesis of iron and nickel-based catalysts for levulinic acid production from cellulose and glucose - Akhlisah, Zulkipli Nor; Wan Azlina, W. A.K.G.; Yunus, Robiah; Taufiq-Yap, Yun Hin; Rashid, Umer; Abdulkareem-Alsultan, G.; Asikin-Mijan, N. (OICC Press, 2026)
The study explores the catalytic performance of nickel (Ni) and iron (Fe)-based catalysts synthesized through precipitation, activation by hydrothermal reaction, and calcination for the conversion of cellulose and glucose into levulinic acid (LA). Characterization of the catalysts was conducted using X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) analyses, which confirmed the formation of metal oxides, specifically NiO and Fe2O3, in the synthesized catalysts. The key experimental parameters, including catalyst loading, reaction temperature, and time, were optimized to improve the LA yield. The Fe.75Ni catalyst achieved the highest catalytic activity, yielding 46.18% based on the theoretical yield or a weight percentage of 29.72 wt.% at a reaction time of 5 hours and 200°C reaction temperature using 0.30g of catalyst. The study highlights the importance of catalyst acidity, good surface area, and thermal stability in enhancing LA production and suggests that the Fe.75Ni catalyst holds significant potential for efficient conversion of biomass.